PENGARUH KNOWLEDGE MANAGEMENT, MOTIVASI KERJA, DAN QUALITY OF WORK LIFE (QWL) TERHADAP KINERJA KARYAWAN PADA PT. INDRABAKTI MUSTIKA DI KENDARI - Putri Bella Frajuli; Ibnu Hajar; Nursaban Rommy Suleman; Sabri Sabri (Pascasarjana Universitas Halu Oleo, 2022)
This study aims: (1) to determine the effect of Knowledge Management, Motivation, and Quality of Work Life on Employee Performance of PT. Indrabakti Mustika In Kendari; (2) to determine the effect of Knowledge Management on Employee Performance of PT. Indrabakti Mustika In Kendari; (3) to determine the effect of motivation on employee performance at PT. Indrabakti Mustika In Kendari; and (4) to determine the effect of Quality of Work Life on Employee Performance of PT. Indrabakti Mustika In Kendari. The sampling technique used in this study was purposive sampling. In this study, samples were taken with the characteristics of male and female employees, all employees with permanent employee status at PT. Indrabakti Mustika. So the number of samples in this study were 50 permanent employees.The results showed that: (1) Knowledge Management, Motivation, and Quality of Work Life simultaneously had a positive and significant effect on the performance of PT. Indrabakti Mustika In Kendari; (2) Knowledge Management, partially positive and significant effect on Employee Performance of PT. Indrabakti Mustika In Kendari; (3) Motivation partially has a positive and significant effect on employee performance at PT. Indrabakti Mustika In Kendari; and (4) Quality of Work Life partially positive and significant effect on Employee Performance PT. Indrabakti Mustika In Kendari